KONSTRUKSI MULTI-AKAD DALAM PRAKTIK KLIPING VIDEO BERBAYAR PADA KAMPANYE DIGITAL : TINJAUAN HUKUM EKONOMI SYARIAH - Imron; Haidar; Hamdani; Krisna (LPPM STAI Muhammadiyah Probolinggo, 2026)
The development of the platform-based digital creative economy has created new forms of transactions involving complex contractual relationships among economic actors. One emerging practice is paid video clipping in digital campaigns, where content creators distribute promotional clips through platform-based task mechanisms. Although increasingly used, the underlying contractual construction has not been widely analyzed from the perspective of Islamic economic law. This study aims to analyze and formulate the multi-contract structure in paid video clipping practices within platform-based digital campaigns. It uses a library research method with a descriptive qualitative approach through conceptual analysis of literature on muamalah fiqh and digital economic studies. The results show that this practice forms a multi-contract configuration involving a wakālah bi al-ujrah contract between the brand and the digital platform and a ju‘ālah contract between the platform and the content creator. Both operate simultaneously in interconnected platform-based transactions. This study demonstrates that the multi-contract approach is a relevant framework for explaining the complexity of transactions in the non-financial digital creative economy and expands its application in Islamic economic law to contemporary digital practices.